Bei zong chan yu zao qi chan zong de xing cheng - McRae, John R. (Shanghai gu ji chu ban she, 2015)
Beschreibung
Translation of : The Northern School and the formation of early Chʻan Buddhism
Keywords: Zen Buddhism / China / History; Zen Buddhism; China